Comparative risk aversion in two periods: An application to self-insurance and self-protection - Tobias Huber (Journal of Risk and Insurance, 2021)
Risk management decisions provide a means to elicit individuals' risk preferences empirically. In such a context, the literature often presumes that the decision to invest in risk management and the benefit of this investment occur contemporaneously. There is, however, no consensus in the theoretical literature that one-period results can be transferred to intertemporal settings. To address this gap, we study the effect of an increase in risk aversion on the demand for risk management in a two-period context. Our findings reproduce the one-period results and, thus, support the focus of previous empirical literature on the structure of the risk rather than on the timing of investments and benefits. We also contrast our results with those obtained by employing widely used but limited preferences to examine risk aversion in intertemporal settings (standard additive expected utility setting, Selden, Epstein and Zin).
Keywords: 330; comparative risk aversion; saving; self-insurance; self-protection